Evidence for Detrimental Cross Interactions between Reactive Oxygen and Nitrogen Species in Leber's Hereditary Optic Neuropathy Cells. (31st December 2015) - Falabella, Micol; Forte, Elena; Magnifico, Maria Chiara; Santini, Paolo; Arese, Marzia; Giuffrè, Alessandro; Radić, Kristina; Chessa, Luciana; Coarelli, Giulia; Buscarinu, Maria Chiara; Mechelli, Rosella; Salvetti, Marco; et al.
Abstract : Here we have collected evidence suggesting that chronic changes in the NO homeostasis and the rise of reactive oxygen species bioavailability can contribute to cell dysfunction in Leber's hereditary optic neuropathy (LHON) patients. We report that peripheral blood mononuclear cells (PBMCs), derived from a female LHON patient with bilateral reduced vision and carrying the pathogenic mutation 11778/ND4, display increased levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS), as revealed by flow cytometry, fluorometric measurements of nitrite/nitrate, and 3-nitrotyrosine immunodetection. Moreover, viability assays with the tetrazolium dye MTT showed that lymphoblasts from the same patient are more sensitive to prolonged NO exposure, leading to cell death. Taken together these findings suggest that oxidative and nitrosative stress cooperatively play an important role in driving LHON pathology when excess NO remains available over time in the cell environment.